ΤΗE PELAGONIAN NAPPE PILE IN NORTHERN GREECE AND FYROM. STRUCTURAL EVOLUTION DURING THE ALPINE OROGENY: A NEW APROACH - Kilias, Ad.; Frisch, W.; Avgerinas, A.; Dunkl, I.; Falalakis, G.; al., et (Bulletin of the Geological Society of Greece, 2010)
The geometry of kinematics and the deformation history of the Pelagonian nappe pile during the Alpine orogeny have been studied in Northern Greece and FYROM. Deformation was started in Middle-Late Jurassic time and was initially associated with ocean-floor subduction followed by ophiolites obduction, nappe stacking and duplication of the Pelagonian continent. The footwall Pelagonian segment from top to bottom was metamorphosed under greenschist to amphibolit facies conditions and a relative high pressure (T = 450o to 620o C and P = 12,5 to 8 kb). Blueschist facies metamorphic assemblages of Late Jurassic age are immediately developed between both hangingwall and footwall Pelagonian segments. Transgressive Late Jurassic-Early Cretaceous neritic limestones and clastic sediments on the top of the obducted ophiolites are maybe related to extension and basins formation simultaneously with the nappe stacking and metamorphism at the lower structural levels of the Pelagonian nappes. Contractional tectonics and nappe stacking continued during the Albian-Aptian time. Simultaneously retrogression and pressure decreasing taken place at the tectonic lower Pelagonian footwall segment. Low grade mylonitic shear zones, possible related to extension, are developed during Late Cretaceous time simultaneously with basins formation and sedimentation of neritic Late Cretaceous to Paleocene limestones and flysch. Intense shortening and imbrication under semi-ductile to brittle conditions occurred during Paleocene to Eocene time resulting the onset of the dome like formation of the footwall Pelagonian segment. The next stages of deformation from Oligocene to Quaternary are related to brittle extension and the final uplift and configuration of the Pelagonian nappe pile.